An In-Depth Comparative Analysis of Science Curricula in Türkiye and Indonesia - Muhammad Ilham Syarif; R. Hariyani Susanti; Şule Erden Özcan; Winda Trimelia Utami (Journal of Natural Science and Integration, 2023)
Government policies, including curriculum development, significantly impact education quality. Indonesia's frequent curriculum changes contrast with Türkiye's 2017 curriculum overhaul. Türkiye outperforms Indonesia in science literacy based on PISA 2018 results. The Merdeka Belajar policy aims to enhance Indonesia's global competitiveness, particularly in STEM education. Curriculum approaches differ, with Türkiye emphasizing practical learning and early physics concepts, while Indonesia relies more on rote memorization. Frequent curriculum changes in Indonesia stem from political and regional factors. This study highlights disparities in PISA scores and curriculum structures, underscoring areas for Indonesia's improvement. Adapting to international standards while considering local contexts is crucial for enhanced science literacy. The research employs a case study methodology, utilizing curriculum documents, interviews, and research articles for analysis, providing insights and recommendations for both countries. Research results indicate that Türkiye's structured curriculum and emphasis on practical learning contribute to its higher science literacy scores compared to Indonesia. In conclusion, this study underscores the need for Indonesia to align its curriculum policies with international standards, while also focusing on fostering critical thinking and practical learning approaches to enhance science literacy outcomes and remain globally competitive in education.Keywords: Curriculum Development; Education Policies; Science Literacy; Comparative Study